Current research and management of undifferentiated pleomorphic sarcoma/myofibrosarcoma - Sun, Haitao; Liu, Jilu; Hu, Fangyuan; Xu, Meng; Leng, Ao; Jiang, Feng; Chen, Kefu (Frontiers in Genetics, 2023)
Undifferentiated pleomorphic sarcoma (UPS), once termed as malignant fibrous histiocytoma, has always been diagnosed exclusively in clinical practice because it lacks any defined resemblance to normal mesenchymal tissue. Although myxofibrosarcoma (MFS) has been separated from UPS due to its fibroblastic differentiation with myxoid stroma, UPS and MFS are still identified as a sarcoma group in terms of molecular landscapes. In this review article, we will describe the associated genes and signaling pathways involved in the process of sarcoma genesis and make a summary of conventional management, targeted therapy, immunotherapy, and some novel potential treatments of UPS/MFS. With the progressive advancements in medical technology and a better understanding about the pathogenic mechanism of UPS/MFS in the coming decades, new lights will be shed on the successful management of UPS/MFS.